A New Combustion Route to Synthesize Mixed Valence Vanadium Oxide Heterojunction Composites as Visible‐Light‐Driven Photocatalysts. Issue 9 (23rd July 2014) - Jiang, Baojiang; Peng, Xiuxia; Qu, Yang; Wang, Hong; Tian, Chungui; Pan, Qingjiang; Li, Mingxia; Zhou, Wei; Fu, Honggang
Abstract The fabrication of a semiconductor heterojunction photocatalyst is a key aim of the visible light photocatalytic field owing to its central role in the enhancement of photogenerated charge separation and quantum efficiency. Herein, a new mixed valence vanadium oxide composite with the VO2@V6O13 heterojunction is fabricated through the facile and direct combustion of an ethanol solution composed of ammonium metavanadate and diethyl imidazole. XRD and TEM analyses reveal the structural evolution at the interface between VO2 and V6O13, which manipulates the electronic structure of the composites. The composition and chemical state of the composites are obtained by using X‐ray photoelectron spectroscopy. In addition, the detailed energy band structure has been confirmed by the analysis of the UV/Vis absorption spectra and X‐ray photoelectron spectroscopy valence band spectra. The mixed valence vanadium oxides readily narrow their energy gap (1.4–2.5 eV), which enables the efficient utilization of visible light and the improvement in charge separation rate. Thus, the photocatalysts with the VO2@V6O13 heterojunction demonstrate improved photocatalytic activity and structural stability in the degradation of atrazine pesticide under visible light irradiation, which is an effective solution for the problem of remnant pesticides for future agriculture. Furthermore, this facile and straightforward method has promising applications in the fabrication of other heterostructure photocatalysts.